Association between grip strength and albuminuria in the general United States population: NHANES 2011–2014 - Yan, Laisha; Hu, Xiaoyan; Wu, Shanshan; Chen, Lina; Zhao, Shunying (Frontiers in Public Health, 2024)
Background Grip strength has been shown to be associated with chronic renal insufficiency, but the relationship between grip strength and albuminuria has not been confirmed. In this study, we used NHANES data to explore the association between grip strength and albuminuria in a US population. Methods In this analytical study, we utilized data sourced from the National Health and Nutrition Examination Survey (NHANES), specifically spanning the years 2011 to 2014. The dataset included 9,638 participants aged 20 years or older. After adjusting for potential confounders, multiple regression models were developed to infer the interrelationship between grip strength and albumin to creatinine ratio (ACR), and subgroup analyses were conducted. Results After adjusting for all covariates, ACR by 0.49 mg/g [−0.49 (95% CI: −0.93, −0.04)] for each 1 kg increase in grip strength decreased. Subgroup analysis showed that gender, age, hyperlipidemia, hypertension, diabetes mellitus, smoking, alcohol consumption and body mass index did not influence the negative correlation between grip strength and albuminuria. Conclusion There is a negative correlation between grip strength and albuminuria in the general U.S. population.